The limits of the GDPR’s subject access request and its impact on the security of the data subjects data - Šavdins, Artūrs (Riga Graduate School of Law, 2020)
The first part of the thesis describes the concepts and definitions of the EU data protection law and will provide a general opinion of the meaning of the SARs and the GDPR. The author tries to find out the main idea of why the legislators decided to introduce the GDPR in the first place and what are the most significant changes that will affect the data controllers and processors. The second part focuses on the data subject access request right, and describes all the limitations and possibilities that come out of this right and how the data controllers and processors should act when SARs received. The third part is devoted to an analysis of SARs impact on the data security and provides some valuable answers to the research questions.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection